PENGARUH LINGKUNGAN KERJA, BUDAYA ORGANISASI, DAN DISIPLIN KERJA TERHADAP KINERJA SATUAN POLISI PAMONG PRAJA KABUPATEN SUKOHARJO - sunaring asriani; Ahmad Husin; Agus Triatmono (JURNAL ILMIAH EDUNOMIKA, 2025)
The effect of work environment, organizational culture, and work discipline on the performance of the police unit of sukoharjo district. This research was conducted at Satuan Polisi Pamong Praja Kabupaten Sukoharjo. The place was chosen because there was a problem there, namely that not all employees had good performance. In addition, in that place, researchers can gain access to find research data. The population in this study were all employees of the Civil Service Police Unit of Sukoharjo Regency, totaling 84 people. The sampling technique used in this study was the nonprobability sampling technique. Therefore, the population in this study was relatively small, namely 84 people, the entire population was used as a sample (saturated sampling). The sample in this study was taken from the target population of 84 people. The method used to obtain data used questionnaires and documentation. The data analysis tool used SPSS. Keywords : Work Environment, Organizational Culture, Work Discipline, Performance